Micronutrient levels among aborigines in Pahang and Perak - Ismarulyusda Ishak,; Zaleha Md Isa,; Jamaludin Mohamed,; Khairul Osman,; Iskandar Zulkarnain Alias,; Khalid Abdul Kadir,; Osman Ali, (Department Of Community Health, Faculty of Medicine, Universiti Kebangsaan Malaysia, 2005)
Micronutrients are essential component of human life. Only small amounts are required for normal growth. The objective of this study was to assess micronutrient status among aborigines living in Sg Siput (U), Perak and Kuala Lipis , Pahang. Our study showed that serum selenium, manganese, magnesium and zinc levels for aborigines were 0.517+0.243pmol/l (n=442), 0.221+0.016pg/l (n=457), 1.178+0.221 mmol/l (n=455) and 15.8472+1.348pmol/ (n=453) respectively. In general, serum selenium and manganese among aborigines were deficient compared to the levels of other population, whilst their serum magnesium and zinc were normal when compared to others population.